2019
DOI: 10.1136/tobaccocontrol-2018-054734
|View full text |Cite
|
Sign up to set email alerts
|

Changes in roll-your-own tobacco and cigarette sales volume and prices before, during and after plain packaging legislation in the UK

Abstract: BackgroundPlain packaging and minimum pack size legislation for tobacco products was introduced in the UK in May 2016, with a 1-year sell-off period until May 2017, during which both fully branded and plain packs of various sizes were legally available. This study investigates trends in prices of roll-your-own tobacco (RYO) before, during and after implementation of this legislation, and compares trends with those observed in the cigarette market.MethodsWe used Nielsen Scantrack data for the period from March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…In our previous studies using Nielsen Scantrack data we demonstrated that plain packaging legislation was associated with an increase in price for both cigarettes [3] and RYO tobacco [10] above the expected tax increase and inflation. However, our results on purchase and price trends for legal pack sizes presented here have shown that even though consumers switched to bigger pack size cigarette products, they paid a lower average price per cigarette, closer to that of the 11 to 19 cigarette packs available before the new policy was implemented, by moving down by one price quartile to cheaper products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies using Nielsen Scantrack data we demonstrated that plain packaging legislation was associated with an increase in price for both cigarettes [3] and RYO tobacco [10] above the expected tax increase and inflation. However, our results on purchase and price trends for legal pack sizes presented here have shown that even though consumers switched to bigger pack size cigarette products, they paid a lower average price per cigarette, closer to that of the 11 to 19 cigarette packs available before the new policy was implemented, by moving down by one price quartile to cheaper products.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous study [10], we used purchases of minimum plain pack sizes (20 cigarettes or 30 grams of RYO per pack) as a proxy marker for plain package sales. To define successive stages of the extent of purchasing of minimum plain pack sizes, which increased gradually during the implementation period [3,10] we created a policy implementation variable with the following categories: before May 2016, 0 to 6 months after May 2016, 7 to 12 months after May 2016, and more than 12 months after May 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This also follows previous literature that has used similar data. [13][14][15] FM products were classified as being in either 'fully branded packaging' which is the old-style colourful packaging sold in a variety of stick sizes, or standardised packaging 19 which was introduced in the UK between May 2016 and May 2017. Branded packaging could further be either price-marked (price printed on the packaging) or non-price-marked.…”
Section: Nielsen Scantrak Datamentioning
confidence: 99%
“…The effects of the implementation of the FCTC encouraged various countries including Australia, the UK, and France to adopt plain packaging for tobacco products [6][7][8]. The growing body of research reveals that plain packaging decreases tobacco use and sales, as well as government health costs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%